Impact of internal business communication on the employees commitment in tourist enterprises - Novaković-Božić Nataša; Perić Goran; Cogoljević Vladan (Trendovi u Poslovanju)
Internal communication is a fundamental component of the company's successful development and has a direct impact on the efficiency, commitment, satisfaction and motivation of employees. Internal communication is directly related to the company's goals and represents the basis of strategic management. Companies should strive to establish an optimal system of internal communication, in order to build quality relations among employees, team spirit, commitment, improvement of the motivation system, as well as an incentive for innovation and initiative. The aim of this paper is to analyze the impact of internal business communication on the commitment of employees in tourism companies. Research results show that internal business communication has a positive impact on employee commitment. Managers in companies that deal with tourism must take into account the advantages of internal business communication and the opportunities brought by its adequate use, when it comes to the impact on the commitment of employees. Modern tourism companies in the world pay more and more attention to internal communication and its effects, so Serbian tourism companies also follow the example of positive business practices and thus improve the commitment of employees.